Effect of Debt to Asset Ratio, Total Asset Turnover, Receivable Turnover, and Sales Growth, on Return on Assets in Property, Real Estate & Construction Companies Listed on the Indonesia Stock Exchange for the 2015-2018 Period - Tania; Cindy; Danny Tan Jaya; Deasy Arisandy Aruan (Institute of Computer Science (IOCS), 2021)
This study aims to understand the impact of DAR, TATO, Receivable Turnover, and Sales Growth on ROA in Property, Real Estate & Construction Companies listed on the IDX 2015-2018. This study uses a sample of 43 Property, Real Estate & Construction companies listed on the IDX in 2015-2018. This research is a quantitative research. The data used are secondary data obtained through the site www.idx.co.id. The method used is purposive sampling. The method of data investigation used is multiple linear regression method. The results show that according to partial DAR has a negative and significant impact on ROA, TATO, and Receivable Turnover have a positive and significant impact on ROA, and Sales Growthhas not significant effect on ROA in Property, Real Estate & Construction companies listed on the IDX in the 2015-2018. Simultaneously, DAR, TATO, Receivable Turnover and Sales Growth have a significant impact on ROA in Property, Real Estate & Construction companies listed on the IDX for the period 2015-2018.